Four new anthraquinones from a soil actinomycete Streptomyces sp. WS-13394 and their bioactivities. Issue 4 (16th February 2018) - Wu, Zhaoyuan; Zhang, Yani; Fang, Wei; Shi, Liqiao; Wan, Zhongyi
Abstract: Further chemical study of secondary metabolites from the soil actinomycete Streptomyces sp. WS-13394 resulted in the isolation of four new alkylated anthraquinone analogues (5 –8 ). Their structures were elucidated on the basis of extensive spectroscopic analysis, including HR-ESI-MS, 1D and 2D NMR. The new compounds, together with analogues obtained before (1 –4 ), were tested for their in vitro cytotoxicity against Huh-7 and SGC-7901. Abstract :